The Potato Crop Its Agricultural, Nutritional and Social Contribution to Humankind - Campos, Hugo; Ortiz, Oscar (Springer Nature, 2020)
Life sciences; Agriculture; Nutrition   ; Plant breeding; Food-Biotechnology; Agricultural economics